Design of Watering and Ambient Temperature Control of Pakcoy Aeroponic Plants with IoT-Based Telegram Notification - Kurniawan Yulianto, Muhammad; Suprianto, Bambang (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2025)
Plant cultivation with hydroponic techniques involves using water or nutrient-rich solutions without soil, focusing on meeting plants' nutritional needs efficiently. Among various hydroponic methods, aeroponics stands out by growing plants in air and providing nutrients via water mist. This method minimizes resource use and enhances plant growth. This research aimed to develop an IoT-based control system for watering and temperature management of pakcoy aeroponic plants, with real-time monitoring via Telegram notifications. The system uses an ESP32 microcontroller to manage watering schedules through an NTP server and regulate temperature with a DS18B20 sensor and a DC fan. The integration of IoT allows farmers to monitor and control the system remotely. Results demonstrated the system's effectiveness in maintaining optimal conditions for pakcoy growth, ensuring efficient resource use, and providing reliable notifications. The proposed system offers a practical solution for optimizing aeroponic cultivation, potentially enhancing productivity and resource management for urban agriculture